Circadian Clock Genes REV-ERBs Inhibits Granulosa Cells Apoptosis by Regulating Mitochondrial Biogenesis and Autophagy in Polycystic Ovary Syndrome - Sun, Lihua; Tian, Hui; Xue, Songguo; Ye, Hongjuan; Xue, Xue; Wang, Rongxiang; Liu, Yu; Zhang, Caixia; Chen, Qiuju; Gao, Shaorong (Frontiers in Cell and Developmental Biology, 2021)
Polycystic ovary syndrome (PCOS) is an endocrinopathy with complex pathophysiology that is a common cause of anovulatory infertility in women. Although the disruption of circadian rhythms is indicated in PCOS, the role of the clock in the etiology of these pathologies has yet to be appreciated. The nuclear receptors REV-ERBα and REV-ERBβ are core modulators of the circadian clock and participate in the regulation of a diverse set of biological functions. However, in PCOS, the expression of REV-ERBs and their effects remain unclear. Here, we demonstrate that the levels of REV-ERBα and REV-ERBβ expression were lower in the granulosa cells of PCOS patients than in control subjects. In vitro, we found that the overexpression of REV-ERBα and REV-ERBβ, and their agonist SR9009, promoted the expression of mitochondrial biosynthesis genes PGC-1α, NRF1, and TFAM and inhibited autophagy in KGN cells. Our results also indicate that REV-ERBα and REV-ERBβ can inhibit apoptosis in granulosa cells and promote proliferation. Importantly, the REV-ERB agonist SR9009 ameliorates abnormal follicular development by promoting mitochondrial biosynthesis and inhibiting autophagy in a mouse PCOS model. This allows us to speculate that SR9009 has potential as a therapeutic agent for the treatment of PCOS.